Applications of Massage in Children from the Perspective of Persian Medicine - Fatemeh Behdad; Fataneh Hashem-Dabaghian (Tehran University of Medical Sciences, 2020)
In Persian medicine (PM), massage is one of the principles for maintaining health.  This study presents the viewpoint of PM about massage in pediatrics and the scientific evidence for its efficacy.  The PM textbooks including Canon of Medicine, Mufarrah al-qulub, Kholase-alHekmah, Kholase-al-Tajareb, Tadbir al-hobali val atfal va-sebyan, Exir-e-Azam, Ehya-al-Atfal, Risalat-al-Dallakieh were reviewed for applications of massage in children. The keywords were Dalk, Ghamz, rubbing, and massage. The effectiveness of PM recommendations for massage in modern medicine was searched in Google Scholar, PubMed, Scopus and science direct, SID, and Magiran with the keywords massage, pediatrics, and children. The selection criteria were clinical trials or reviews on pediatric massage in English or Persian language without time limitation. Applications of pediatric massage in PM which scientific articles approve their efficacy include facilitating the growth, development, and weight gain, reducing muscle and joint pain, relieving colic and bloating, helping to treat skin dryness, and convulsion. Other applications including sore throats, colds, vomiting, and eye aberrations are needed to be evaluated in clinical studies.